PERILAKU RAMAH AIR DALAM PERSPEKTIF HUKUM(STUDI PERATURAN DAERAH DKI JAKARTA DAN KOTA DEPOK TERKAIT SUMBER DAYA AIR) - Dewi, R. Ismala; Nurdin, Aad Rusyad (UI Scholars Hub, 2021)
Various water resource problems that occur in Indonesia, including in DKI Jakarta and surrounding cities, such as flooding, drought, raw water crisis, river water pollution, have an impact on decreasing water availability. This is partly due to the unfriendly behavior of the community in using water, especially those in water catchment areas. Therefore, it is necessary to manage waterto maintain the sustainability of water availability so as to provide fair benefits to the community. Given these objectives and the existence of complex water problems, it requires adequate regulation. A rule that is not only to overcome the act of destroying the environment/water resources, but also to be able to encourage behavior in order to prevent or at least reduce the occurrence of environmental damage. Therefore, it is necessary to study how the rule of law, in this case the Regional Regulation (Perda) of DKI Jakarta and the city of Depok in regulating the environment/water resources is related to the behavior of the people who are friendly to water. The approach taken in this study is normative juridical towards Regional Regulations (Perda).